2022
DOI: 10.3390/life12071062
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Bioimpedance Analysis as a Predictor of Injury and Performance Status in Professional Basketball Players: A New Application Potential?

Abstract: Bioelectrical impedance vector analysis (BIVA) is a technique used for the assessment of body composition based on the electrical properties of biological tissues and for evaluating variations related to hydration and nutrition status changes. The present study aimed to investigate the possibility of predicting performance status and injuries using segmental BIVA analysis. Data were collected from 14 professional male athletes aged between 20 and 39 years of Caucasian and Afro-American ethnicity belonging to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Weight and height were measured with a mechanical column scale SECA 700 Eye Level Beam (SECA North America, Medical Measuring Systems and Scales, 13601 Benson Avenue, Chino, CA 91710, USA), using an approximation of 50 g for the weight and 0.1 cm for the height according to the standard methodologies defined in the literature [23]. Utilizing BIVA analysis, the impedance components resistance (Rz) and reactance (Xc) were detected with a bioimpedance analyzer (BIA 101 BIVA PRO, Akern, Florence, Italy) [24][25][26][27][28][29][30], processing the data obtained with the Bodygram Dashboard ® software (Akern, Florence, Italy) [27][28][29][30], using BIATRODES electrodes (Akern, Florence, Italy) [27][28][29][30]. Before performing the BIVA, the subjects were placed supine on a non-conductive surface for at least 5 min, allowing for a homogeneous distribution of fluids.…”
Section: Evaluation Schemementioning
confidence: 99%
See 1 more Smart Citation
“…Weight and height were measured with a mechanical column scale SECA 700 Eye Level Beam (SECA North America, Medical Measuring Systems and Scales, 13601 Benson Avenue, Chino, CA 91710, USA), using an approximation of 50 g for the weight and 0.1 cm for the height according to the standard methodologies defined in the literature [23]. Utilizing BIVA analysis, the impedance components resistance (Rz) and reactance (Xc) were detected with a bioimpedance analyzer (BIA 101 BIVA PRO, Akern, Florence, Italy) [24][25][26][27][28][29][30], processing the data obtained with the Bodygram Dashboard ® software (Akern, Florence, Italy) [27][28][29][30], using BIATRODES electrodes (Akern, Florence, Italy) [27][28][29][30]. Before performing the BIVA, the subjects were placed supine on a non-conductive surface for at least 5 min, allowing for a homogeneous distribution of fluids.…”
Section: Evaluation Schemementioning
confidence: 99%
“…The lower limbs were abducted with an opening at 45 • with respect to the midline of the body, and the upper limbs were abducted at 30 • with respect to the trunk, verifying the absence of contact between the lower limbs, upper limbs, and trunk, and with any potentially conductive object. The skin was cleansed with alcohol at the points of application of the four electrodes (two injectors and two detectors), which were positioned on the back of the right hand, in correspondence with the radioulnar joint and the metacarpophalangeal joint of the third finger for the upper district, and on the back of the foot, one on the tibiotarsal joint and the other in correspondence with the metatarsophalangeal joint of the third for the lower section [24][25][26][27][28][29][30], respecting the distance of 5 cm from each other. The data obtained were processed using the Bodygram Dashboard software by analyzing the direct values and obtaining relatively derived estimates.…”
Section: Evaluation Schemementioning
confidence: 99%
“…Bioelectrical impedance analysis (BIA) is commonly used to assess body composition based on the electrical characteristics of biological tissue by sending a weak electrical current through the body [17]. One property of electric current is that depending on its frequency, it flows along highly conductive body tissues [18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that it is possible to predict, with a good margin of accuracy, a result that can be superimposed on the evaluation of the somatotype according to Heath–Carter through a BIVA evaluation [ 18 , 19 , 20 , 21 ]. Furthermore, correlating with other parameters such as muscle quality, performance, and injury indices [ 22 , 23 ] suggests how probable the compositional and morphological study of the organism carried out with different techniques can represent two different points of view, which, when suitably integrated, are able to provide the same information with a good level of overlap.…”
Section: Introductionmentioning
confidence: 99%